CANDİDA ALBİCANS’DA MANNAN: ÇEŞİTLİ ÖZELLİKLERİ VE ÖNEMİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background.- Candida albicans is both a commensal and opportunistic pathogen of humans. The outermost cellular structure, the cell wall play an essential role in the interactions with the host. Most of biological functions related to pathogenicity and virulence reside in the fungal cell wall. Mannoproteins, the major cell wall components of Candida albicans are a significant source of antigens. Both the carbohydrate and protein moieties are able to trigger immune response. The carbohydrate and/or protein parts may also be the candidal adhesin to bind host ligands and may contribute to hydrophobic interactions. Mannoprotein was demonstrated to cause haemolysis promoting the disruption of human red blood cells as well as to prevent phagocytosis. This review will adress the significanse features of Candida albicans cell wall mannoproteins.